Investigation of bankruptcy in shipping industry - liner shipping - Lau, Rui Wen (2018)
In liner shipping, the demise of Hanjin Shipping (HJS) in 2016 has shocked the industry as a whole and created several problems across the supply chain. Despite the extreme consequences, not much research has been done in relation to the fundamental reasons of bankruptcies. Thus, the immediate objective of this paper is to investigate the underlying reasons behind bankruptcies from 1986 to 2016 so as to provide a better understanding to adapt to the competitive and volatile business landscape.